Analisis Kinerja Karyawan Melalui Konflik Peran dan Stres Kerja - Chandra, Felix; Maghfirah, Nurul; Muntahar, Nurul Hijrah (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
This study aims to determine the effect of role conflict and work stress on employee performance. This type of research is explanatory. This research was conducted at PT. Wahana Lestari Investama, with a population in this study totaling 430 people. The sample studied amounted to 60 people obtained by using the purposive sampling method with the criteria of being female employees who are married and have children. The measurement scale used is the Likert scale. Data in this study were collected by distributing questionnaires to respondents. The data analysis technique used to test the hypothesis is multiple regression with the help of the SPSS tool. The results showed that the role conflict had a significant negative effect on employee performance, and work stress had a significant negative effect on employee performance.